Functional study and transcriptomic signatures confirm an application of induced microglia cellular model for studying Alzheimer's disease: Developing topics. (7th December 2020) - Banerjee, Atoshi; Lu, Yimei; Do, Kenny; Wu, Xiaogang; Mize, Travis; Chen, Jingchun
Abstract: Background: Microglia are specialized immune cells of the brain that maintains brain homeostasis. Amyloid protein accumulation due to inefficient microglial phagocytosis or neuroinflammation due to microglia polarization has been linked to Alzheimers disease (AD) progression. However, the lack of human microglia or microglial cellular model makes it difficult to understand the exact microglial functions underlying the disease. Method: We established in vitro cellular model of induced microglia‐like cells (iMGLCs) from human peripheral blood monocytes. The iMGLCs were first characterized by morphology and microglial markers. Functional study specific to microglia was established by phagocytic capacity and polarization properties. Further RNA‐Seq was performed to determine the consistency of microglia signatures with brain‐resident microglia. Result: iMGLCs exhibited ramified morphology (a typical shape of resting microglia from brain) and expressed unique microglial markers such as TMEM119 and P2RY12. Functional study showed that iMGLCs could phagocytose amyloid beta protein and polarized to M1 (proinflammation) or M2 (anti‐inflammation) state upon specific stimulation. RNA‐Seq analysis indicated that iMGLCs were distinguished from monocytes but closely clustered with induced macrophages and brain‐resident microglia. TREM2 and APOE were two genes among the most differentially regulated genes in iMGLCs that participate in pathways related to immune response and cholesterol metabolism. Conclusion: Our data highlights the functions and transcriptomic signatures of iMGLC model which can be further delineated for studying neuroinflammation in AD and discovery of new targets for treatments.